Analisis Pemerataan Distribusi Panas pada Permukaan Material Plastik pada Alat Mesin Press Sealing - Indra Koto; Aken Derisman; Josua Amindo Tua Manurung; Cavin Ananda Teguh S (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Uniform heat distribution across plastic materials is a critical aspect of manufacturing processes such as molding and thermoforming. Irregularities in temperature distribution can lead to product defects, including deformation, uneven shrinkage, and compromised surface quality. This study aims to analyze the factors influencing heat distribution uniformity on the surface of plastic materials using a sealing press machine. An experimental method was employed to analyze heat distribution on Polypropylene (PP) surfaces using the sealing press. The study relied entirely on primary data regarding heat application specifically temperatures of 110°C, 140°C, and 180°C; a pressure of 3 bar; and a press distance of 0.08 m. The results indicate that heat distribution within the polymer is significantly influenced by the material's thermal conductivity, pressure, duration, press distance, and the conductive heating mode. Variations in the polymer's thermophysical properties result in distinct temperature distribution responses depending on the heating method used.